Phytochemicals: Extraction and Preliminary Investigation of Bioactive Compounds from Rumex Vesicarius and Terminalia Catappa Plant - Suryavanshi, Anandika; Saxena, Anand Murari; Mago, Payal; Khatri, Manisha (Asian Journal of Engineering and Applied Technology, 2019)
The present study was carried out for the determination of bioactive compounds from different extracts of Terminalia catappa and Rumex vesicarius. The plants are mines of several bioactive compounds also called as phytochemical compounds. These bioactive compounds are responsible for imparting such a potential medicinal property in the plants. The medicinal plant contains various types of bioactive compounds including phenols, alkaloids, terpenoids, tannins, glycosides, flavonoids etc. These bioactive compounds take part in various metabolic pathways and impart their effect. Terminalia catappa and Rumex vesicarius are such medicinal plants which are being used for medicinal purposes for long time. Both of them are rich source of potential bioactive compounds and hence carry out several biological activities effective for the treatment of various diseases. Hence the study focuses on determining the types of bioactive compounds they acquire. For this the leaves of T. catappa and dry stems of R. vesicarius were used for the extraction using different solvents with soxhlet method. The extract of different solvents was analyzed for the phytochemical test. The results obtained revealed that the type of solvents is crucial in determining the type of bioactive compounds to be present in extract. The results showed that ethanol and methanol are good solvent choice for extraction for these two plants. The results concludes that the presence of such potential and effective bioactive compounds in their extract makes them important medicinal plants and are hence employed for several researches and also used for treatment of various kinds of diseases.